Impact of Heat Stress on the Physiological Responses of Sheep - Aishvarya R. Jumnake; Vishwambhar R. Patodkar; Vikas M. Sardar; Prajwalini V. Mehere; Sameer N. Jadhav; Sachin S. Pawar (Contemporary Research and Perspectives in Biological Science Vol. 5, 2024)
The Madgyal sheep breed is an indigenous breed in the Jat taluka in Sangli District. Abachiwari, Gholeshwar, Kunikonur, Madgyal, Pandozari, Sanamadi and Sonyal are prominent villages having typical Madgyal sheep. This sheep breed derives its name from the Madgyal village in Jat tehsil of Sangli.The aim of the study is to investigate the impact of heat stress on physiological parameters in sheep, Madgyal sheep were exposed to 0,4 and 8 hrs heat of direct sunlight during grazing in 3 different Groups Viz A, B and C. The study was conducted on Day 0, Day 15 and Day 30 of the experiment to observe the effect of different durations of heat exposure on all physiological parameters. The temperature humidity index (THI) values during the experimental period were found to be (76.28+-0.81). Physiological parameters under study were subjected to statistical analysis using IBM SPSS software by applying Duncan’s Multiple Range Test. The results of the statistical analysis showed that there was no significant difference group-wise and day-wise in the Rectal temperature. However, the Respiration Rate, Pulse Rate and Heart Rate in Group wise comparison showed a significant difference (P<0.05) with an increasing trend. In Day wise comparison of Respiratory Rates there was no significant difference on different days in Groups A & B. However, there was a significant difference (P<0.05) in group C on different days with an increasing trend. Pulse Rate and Heart rate Day-wise comparison showed no significant difference at different days in Groups A and C while there was a significant difference at different days in Group B with higher values at Day 15 and Day 30 as compared to at Day 0. Changes in all these physiological parameters can relate to the coping mechanism of Madgyal sheep during heat stress.